Konsep Naturalisasi Ilmu Dalam Persepektif Abdelhamed Sabra - Ernita Dewi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
Naturalization is a process of adopting a new branch of knowledge from foreign place to suit the local culture where the knowledge is being developed. When the new branch of knowledge come to the Islamic community, the Islamic scholars try to adjust it in order to comply with the Islamic values, called Islamization. The term was first proposed by Abdelhamed Sabra in an attempt to answer Pierre Dhume who claimed that Islamic thinkers adopted Greek philosophy without critical analysis. Sabra argued that Islam is not passive and does not accept the knowledge from the ancient Greek for granted. Islamic thinkers have developed Greek philosophy with a string analysis yielding a new knowledge relevant to Islam. The process of knowledge naturalization took place when Islamic culture encountered with Greek and Roman culture. Not all knowledge from Greek was accepted by Islamic thinkers. Every new knowledge has gone through a tight verification so that it can be developed in the Islamic world